Angiotensin Converting Enzyme (ACE) insertion/deletion (rs1799752) gene polymorphism and bladder cancer aggressiveness in Egyptian patients: A pilot case-control study - Nora Atia; Yasser Osman; A. F. Abdel-Aziz; Sherif Refaat; Mohamed R. Khalil; Manar Refaat (Molecular Biology Reports, 2026)

IL-27–964 A/G polymorphism promoter polymorphism, serum IL-27, and vitamin D in multiple sclerosis: evidence from an egyptian case–control study - Hend Mousa; Nora M. Elkady; Manar Refaat; Omali Y. El‑khawaga (Molecular Biology Reports, 2026)

Quassia amara Linn. (Simaroubaceae): phytochemical composition and biopesticidal potential - Mohamed E. Mostafa; Ahmed Ramadan El-Rokh; Mamdouh Abdel-Mogib; M. Abd El Salam; Reda A. El-Sharkawy; Manar Refaat; Ghada N. El-Masry; Ahmed E. M. Abd El-Mageed; Amal F. Soliman (Journal of Plant Diseases and Protection, 2025)
Piercing-sucking pests infest many strategic crops worldwide, causing significant damage to crops. Botanical natural products provide several promising pesticide agents that could control these pests as an alternative to the negatively impacted synthetic insecticides. Bioassay-guided separation of the alkaloid fraction of Quassia amara Linn. woody parts against two serious pests ( Aphis craccivora Koch and Tetranychus urticae Koch) and resulted in the isolation of a new alkaloid, a β -carboline derivative 3 named quassianine, along with two known alkaloid compounds named harmine 1 and gardnerine 2 were isolated for the first time from this species using extensive chromatographic techniques. The structure elucidation of the isolated compounds was established via various 1D and 2D NMR and ESI–MS analyses. The susceptibility of both tested pests was assessed under laboratory conditions for the alkaloid and non-alkaloid fractions of Q. amara , the three pure isolated compounds and the positive control azadirachtin (Okios 3.2% EC). The alkaloid fraction was found to be the most potent fraction against A. craccivora and T. urticae with LC 50 values of 4.3 and 79.1 ppm, while harmine 1 was the most potent isolated compound with LC 50 values of 3.7 and 20.3 ppm, respectively. The most toxic alkaloid fraction and harmine compound were formulated and tested against both pests under field conditions using the LC 90 multiplicities. Furthermore, the biochemical parameters of six enzymes belonging to A. craccivora and T. urticae were estimated after the application of the LC 50 value of the alkaloid fraction and harmine 1 . Also, a detailed toxicological study on the non-target organisms, honeybees Apis cerana , coccinellid predator ladybird beetles Coccinella septempunctata and adult albino rats was conducted. Several biochemical investigations (including alanine amino transaminase, albumin, total cholesterol and reproductive hormones), as well as histopathological studies were performed. The results showed that the alkaloid fraction contains many active principles that could serve as a natural pesticide to protect some agricultural crops from many serious pests and are safer than synthetic pesticides for non-target organisms. Therefore, the Q. amara alkaloid fraction may be considered a prototype natural pesticide. Graphical abstract